Measuring R&D tax support Findings from the new OECD R&D Tax Incentives Database - Appelt, Silvia (OECD Publishing, 2019)
Investment in research and experimental development (R&D) is an important driver of innovation and economic growth. Over the past two decades, tax incentives have become a key policy instrument for promoting business R&D. This raises a number of policy questions: How has the role of tax incentives in the R&D support policy mix evolved across OECD countries and other major economies? How generous are tax relief provisions for different types of firms? How effective are they in stimulating business R&D investment? The OECD R&D Tax Incentives Database (http://oe.cd/rdtax) aims to contribute to the data infrastructure available to policy makers and researchers to examine the use and impact of R&D tax incentives across OECD countries and partner economies. This paper provides a practical guide to using this new database, describing the recently released R&D tax incentive data and highlighting their potential for internationally comparative work through descriptive indicators and econometric analysis
Keywords: Science and Technology; Industry and Services